2009
DOI: 10.1021/cb9001415
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent Peptidomimetic Ligands of TrkC Are Biased Agonists and Selectively Induce Neuritogenesis or Potentiate Neurotrophin-3 Trophic Signals

Abstract: This study was initiated to find small molecule ligands that would induce a functional response when docked with neurotrophin Trk receptors. "Minimalist" mimics of β-turns were designed for this purpose. These mimics are: (i) rigid, yet easily folded into turn-like conformations, and (ii) readily accessible from amino acids bearing most of the natural side chains. Gram quantities of sixteen of these turn mimics were prepared, then assembled into 152 fluorescein-labeled bivalent peptidomimetics via a solution-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 55 publications
0
67
0
Order By: Relevance
“…BMS355349 has been described as a selective potentiator of NT-3 mediated TrkA and TrkB receptor activity and has proven to induce neurogenesis (Chen et al 2009; Lewis et al 2006). …”
Section: Future Directions: Targeting Growth Factor Signaling With Symentioning
confidence: 99%
“…BMS355349 has been described as a selective potentiator of NT-3 mediated TrkA and TrkB receptor activity and has proven to induce neurogenesis (Chen et al 2009; Lewis et al 2006). …”
Section: Future Directions: Targeting Growth Factor Signaling With Symentioning
confidence: 99%
“…154 Eight peptidomimetics were identified that bound selectively to TrkC. Five of these, represented by Compound 6E in Figure 5.10B, were shown to potentiate the trophic activity of a submaximal concentration of NT-3 in nnr5-TrkC cells (see above) in a survival assay following serum deprivation.…”
Section: Biased Agonism At the Tropomyosin Receptorsmentioning
confidence: 99%
“…Compound 6F, and the other two differentiation-inducing peptidomimetics, were also able to activate TrkC and Akt, but not MAPK, as shown by tyrosine phosphorylation. 154 Akt activation is known to be important for neurotrophin-induced survival and differentiation, while MAPK activation is primarily associated with cell survival. 123 Unfortunately, the ability of Compound 6E and related peptidomimetics to induce phosphorylation of TrkC and downstream signaling intermediaries was not assessed.…”
Section: Biased Agonism At the Tropomyosin Receptorsmentioning
confidence: 99%
“…Good NGF mimetics at this stage appear to be D3 or its derivatives and LM11A-24 or LM11A-31, although each may potentially be useful for a distinct purpose. Also being developed are TrkB (O' Leary & Hughes, 2003;Fletcher, et al, 2008;Fletcher & Hughes, 2009) and TrkC Chen, et al, 2009;Liu, et al, 2010) antagonists/agonists. BDNF mimetics have made progress toward a useful therapeutic reagent with efficacy studies in rodents (Massa et al, 2010).…”
Section: The Prognosis For Signal Selective Mimeticsmentioning
confidence: 99%